2020
DOI: 10.24018/ejbmr.2020.5.6.589
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Country‐of‐Origin Image on Purchase Intention. The Mediating Role of Perceived Quality and Perceived Price

Abstract: This study aims to evaluate the impact of Country-of-origin image on purchase intention through two mediating variables (perceived quality and perceived price). After a short literature review, an empirical study was conducted among 120 participants. Results indicate that the country-of-origin Image has a positive impact on perceived quality and perceived price. They also highlight the mediating role of perceived price in the relationship between Country‐of‐origin image and purchase intention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Merabet [ 57 ] explored the impact of country of origin image on purchase intention and the variables of perceived quality and perceived price. The study of 120 respondents showed that country of origin image had a positive effect on perceived quality and perceived price, and perceived price mediated the relationship between country of origin and purchase intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Merabet [ 57 ] explored the impact of country of origin image on purchase intention and the variables of perceived quality and perceived price. The study of 120 respondents showed that country of origin image had a positive effect on perceived quality and perceived price, and perceived price mediated the relationship between country of origin and purchase intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Ini menunjukkan bahwa ada banyak pelanggan yang tertarik untuk membeli platform baru untuk video on demand, terlebih lagi dengan harga yang relative murah dari para pesaingnya. Hal ini sesuai dengan penjelasan Merabet (2020), sebagian besar pelanggan memberikan perspektif pada harga dengan nilai subjektif untuk produk seperti "mahal" atau "murah".…”
Section: Pendahuluanunclassified
“…According to customers consciously perceive the country of origin and consider it important when making purchasing decisions. Perceptions of a product's country of origin serve as indicators of its quality and reputation for customers (Merabet, 2020). To this end, it is necessary to create a bond of familiarity between consumers and the product or brand (Creux-Martelli et al, 2023).…”
Section: Introductionmentioning
confidence: 99%